2016
DOI: 10.1248/cpb.c15-00661
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Prenylated Flavonoids from <i>Helminthostachys zeylanica</i>

Abstract: 1) The rhizomes of H. zeylanica are used in a popular antipyretic and anti-inflammatory Chinese herbal medicine known as "Daodi-Ugon." 1,2) This plant has also been shown to exhibit hepatoprotective activity.3,4) Numerous bioactive flavonoids containing prenyl or geranyl groups have been isolated from the rhizomes of H. zeylanica.2-6) Our current systematic phytochemical investigation of this plant led to the isolation of two new prenylflavonoids, neougonins A (1) and B (2), along with nine known flavonoids (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…The crude extract of HZ demonstrated hepatoprotective effects in the traditional use and was proven in previous reports [ 14 , 15 ]. Phytochemical research has reported that HZ is abundant in flavonoids [ 18 , 19 , 20 , 22 , 23 ]. Ugonin M, one of the major flavonoid components of HZ [ 34 ], exhibited both in vitro [ 19 , 23 ] and in vivo [ 24 ] antioxidant and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crude extract of HZ demonstrated hepatoprotective effects in the traditional use and was proven in previous reports [ 14 , 15 ]. Phytochemical research has reported that HZ is abundant in flavonoids [ 18 , 19 , 20 , 22 , 23 ]. Ugonin M, one of the major flavonoid components of HZ [ 34 ], exhibited both in vitro [ 19 , 23 ] and in vivo [ 24 ] antioxidant and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies used the crude extracts of HZ to evaluate the anti-inflammatory effects through in vivo hepatotoxicity [ 14 , 15 ] and acute lung injury models [ 16 ]. Several unique flavonoids isolated from HZ were reported to possess a variety of biological activities including antioxidant activities [ 17 , 18 ], anti-inflammatory activities [ 17 , 19 , 20 , 21 , 22 , 23 , 24 ], melanogenesis inhibitory activities [ 25 , 26 ]; neuroprotection [ 27 ], antiosteoporosis [ 23 , 28 , 29 ], anti-cancer [ 30 , 31 ], and immunomodulatory effects [ 32 ]; and prevention of neointimal hyperplasia and migration [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different prenylated flavonoids have been isolated from Helminthostachys zeylanica (L.) Hook., Fig. 19 Prenylated flavonoids from Helminthostachys zeylanica (Huang et al 2010a, b, c) including the new molecules neougonins A and B, and the previously-described ugonin D,2-(3,4-dihydroxyphenyl)-6-((2,2-dimethyl-6-methylene cyclohexyl)methyl)-5,7-dihydroxy-chroman-4-one, ugonins E, J, L, and S, 4″a,5″,6″,7″,8″,8″a-hexahydro-5,3′,4′-trihydroxy-5″,5″,8″a-trimethyl-4H-chromeno [2″,3″:7,6]flavone, 4″a,5″,6″,7″,8″,8″a-hexahydro-5, 3′,4′-trihydroxy-5″,5″,8″atrimethyl-4H-chromeno[2″, 3″:7,8] flavone, and ugonin N (Su et al 2016). Besides flavonoids, the new peroxy fatty acids thermalic acids A, and B, have been isolated from O. thermal (Dong et al 2016).…”
Section: Ophioglossaceaementioning
confidence: 99%
“…Talang Mamak tribe in Riau use H. zeylanica to treat inflammation, dysentery, cataracts, early-stage tuberculosis, syphilis, diabetic, and malaria. 2 H. zeylanica contains saponins, flavonoids, stilbenes and phenolics and shows various biological activities such as antioxidant, 3,4,5 anti-inflammation, 6,7,8 anti-osteoporotic, 9 and antihyperuricemia. 10 Furthermore, phenolics and flavonoids inhibit α-glucosidase enzyme which is responsible in glucose levels.…”
Section: Introductionmentioning
confidence: 99%